Pengenalan dan Pelatihan Robot In-Line untuk Siswa SMK dalam Konteks Industri dan Green Supply Chain - Suparno, Adizty; Utami, Diah; Yudhistira, Gilang Awan; Wahyuni, Sri (CV. IRA PUBLISHING, 2025)
This community service program introduces in-line robotic technology to vocational high school students in the Office Management major, focusing on administrative automation within a green supply chain framework. Using an educational, participatory approach, the program includes theoretical material, case studies, hands-on robot assembly, and reflective discussions. Results show that students grasped basic robotic concepts, automation workflows, and their relevance in supporting efficiency and reducing administrative waste. This technology-based learning promotes students' competency in adapting to digital office environments and modern workplaces. Questionnaire-based evaluation revealed that improvements are needed to better align the theme with student interests and to optimize supporting facilities.